Plant physiology - Taiz, Lincoln; Zeiger, Eduardo (Sunderland, Mass. : Sinauer Associates, Incorporated, Publishers, 2002)
Extensively streamlined and revised for clarity, this thoroughly updated third edition provides an introduction to plant physiology suitable for both undergraduate and graduate students. The volume's three units cover transport and translocation of water and solutes; biochemistry and metabolism; and growth and development. Material considered basic for plant physiology courses, as well as more advanced material from the second edition, has been removed from the text and posted on an affiliated Web site. The interactive Web component is keyed to textbook chapters and referenced from the book. The volume includes many new and revised figures and color photographs, study questions, and a glossary of terms. Annotation c. Book News, Incorporated, Portland, OR
Contents t t t t t t t t t t t t t t t t
Includes bibliographical references and index.
Keywords: Plant physiology